Dementia care in acute hospitals: A framework for practice development and theory‐based evaluation - Melanie Karrer; Adelheid Zeller; Hanna Mayer (Wiley, 2023)
Abstract Aim The aim was to generate a framework for dementia care in acute hospitals. Design Framework development with logic modelling. Methods In phase one, we identified relevant elements of the framework by analysing several sources and by critically discussing them within the research team. We created the framework with logic modelling. In phase two, we adapted the framework in expert workshops and by reanalysing the included sources. We used the first stage of CReDECI 2 checklist for reporting. Results The framework describes necessary activities within four main bundles of measures: "developing structures and processes," "developing competences and attitudes," "building relationships" and "ensuring a social environment and adequate stimulation." The overarching outcome is a person‐centred hospital culture, manifesting itself on different levels. The framework illustrates the necessity of an organization‐wide person‐centred culture for achieving positive outcomes for people with dementia, their relatives and health professionals.